Dynamic self-assembled polymer: HCl responsive inversion of supramolecular polymer handedness. Issue 74 (6th October 2017) - Paikar, Arpita; Haldar, Debasish
Abstract : Discotic trisamide formed a self-assembled polymer and exhibits inversion of supramolecular polymer handedness in the presence of HCl. Abstract : A series of discotic tricarboxyamides with varied amino acid side arm functionality and their HCl responsive diverse self-assembly behavior and formation of dynamic polymer is studied. Discotic trisamide1 obtained from Boc protectedl -Lys self-assembled into a long fibrillar aggregate-like supramolecular P helical polymer. However, on addition of HCl, the supramolecular helical handedness of the assemblies is completely inverted. Irrespective of the chiral centres configuration, supramolecular chiral bias is arising from molecular conformations. FE-SEM reveals the formation of right handed entangled polymeric fibers. However, left handed entangled fibers have appeared on addition of 0.12 M HCl. The trisamide2 containing Boc protectedl -Trp exhibits disk like morphology both in the presence and absence of 0.12 M HCl and does not show a change of supramolecular handedness. This demonstrates how remarkably distinct morphologies originate from stimuli responsive building blocks assembled in a subtly different manner.